Le récit triptyque par la musique - L’exemple des films de Kim-Ki-duk - Hwarim Cho; Giusy Pisano (Mise au Point, 2013)
This article suggests analyzing the construction of cinematic narrative through a particular example: the work of South Korean filmmaker Kim Ki-duk. The specific devices used – mixing free and indirect subjective, objective direct narrative and subjective direct narrative, along with Western and Oriental cultural references - invites to reflect on several parameters staging visually and audibly. We will focus our attention on one of the most appropriate elements here, the music, because far from being a simple illustration, it is the vector of this complex composition.